Marginal leakage of amalgam and modern composite materials related to restorative techniques in class II cavity (Comparative study) - Mohammad K Sabah; Luma M Baban (College of Dentistry/ University of Baghdad, 2014)
Background: Restoration of the gingival margin of Class II cavities with composite resin continues to be problematic, especially where no enamel exists for bonding to the gingival margin. The aim of study is to evaluate the marginal leakage at enamel and cementum margin of class II MOD cavities using amalgam restoration and modern composite restorations Filtek P90, Filtek Z250 XT (Nano Hybrid Universal Restorative) and SDR bulk fill with different restoratives techniques. Materials and method: Eighty sound maxillary first premolar teeth were collected and divided into two main groups, enamel group and cementum group (40 teeth) for each group. The enamel group was prepared with standardized Class II MOD cavity with gingival margin (1 mm above C.E.J) on both box sides. While the cementum group with the gingival margin (1 mm below C.E.J) on both sides. The enamel and cementum groups were then subdivided into eight subgroups for each (five teeth) with 10 boxes for each group. Subgroups within the main group named according to materials and techniques that were used with it as following: Amalgam subgroup (Permite, SDI), SDR subgroup (DENTSPLY) with bulk technique, Filtek P90 subgroup (3M ESPE) with three incremental techniques (Oblique, Horizontal and Centripetal technique), and Filtek Z250XT subgroup (3M ESPE) with three incremental techniques (Oblique, Horizontal and Centripetal technique).After specimens were stored in distilled water at 37C for 7 days. All specimens were subjected to thermocycling at (5 to 55 C). Microleakage was evaluated by stereomicroscope (20 X). Data were analyzed statistically by Kruskal-Wallis test and Mann-Whitney U-test. Result: All experimental groups showed leakage at cementum more than enamel groups. SDR bulk fill subgroup showed the highest marginal leakage among all experimental groups followed by Filtek Z250 XT subgroup with horizontal technique at both enamel and cementum groups. Silorane and Filtek Z250 XT subgroups with oblique technique showed the least marginal leakage followed by centripetal technique at both enamel and cementum groups. Amalgam restoration subgroup shows lesser leakage than SDR bulk fills subgroup significantly at both enamel and cementum groups. While it show higher leakage than Silorane subgroup with oblique technique significantly at enamel margin only. Conclusion: The limiting factors for marginal leakage are technique and material dependent.